Numerical simulation of the performance of the a-Si：H/a-SiGe：H/a-SiGe：H tandem solar cell - 柯少颖 王茺 潘涛 杨杰 杨宇 (Journal of semiconductors, 2014)
The computer program AMPS-1D（analysis of microelectronic and photonic structures） has been employed to simulate the performance of the a-Si：H/a-SiGe：H/a-SiGe：H triple-junction solar cell at the radiation of AM1.5G（100 mW/cm2/ and room temperature. Firstly, three sub-cells with band gaps of 1.8, 1.6 and 1.4 eV are simulated, respectively. The simulation results indicate that the density of defect states is an important factor, which affects the open circuit voltage and the filling factor of the solar cell. The two-step current matching method and the control variate method are employed in the simulation. The results show that the best solar cell performance would be achieved when the intrinsic layer thickness from top to bottom is set to be 70, 180 and 220 nm, respectively. We also optimize the tunnel-junction structure of the solar cell reasonably, the simulation results show that the open circuit voltage, filling factor and conversion efficiency are all improved and the S-shape current density–voltage curve disappears during optimizing the tunnel-junction structure. Besides, the diagram of the energy band and the carrier recombination rate are also analyzed. Finally, our simulation data are compared to the experimental data published in other literature. It is demonstrated that the numerical results agree with the experimental ones very well.